(Table 1, page 119) Analysis of ferromanganese concretions from Oneida Lake, U.S.A. and Lake Alstern, Sweden - Krishnaswami, Seth; Moore, Willard S (Supplement to: Krishnaswami, S; Moore, WS (1973): Accretion Rates of Freshwater Manganese Deposits. Nature Physical Science, 243(129), 114-116, https://doi.org/10.1038/physci243114a0, 1973)
2 nodules, one spherical, similar to 2 cm diameter form L. Alstern, Sweden the other saucer-shaped, similar to 2 cm thick from L. Oneida, New York were studied by using 228Ra and super(210)pb in order to measure accretion rates in the range 100-1000 mm/10 super(3) year. The deduced rates are 1.4 and 2.6 mm/ 10 super(3) year. Respectively. The author discuss the problems of how deep sea noducles stay at the sediment-water interface when the sediment around them is accumulating 1000 times faster than the nodules themselves.